The Impact of Fiscal Policy on China’s High-End Manufacturing Industry - Liu, Jiasong (Transactions on Economics, Business and Management Research, 2024)
In recent years, with China facing increasing technological embargoes and sanctions, the Government has started to prioritize the development of high-end manufacturing as a key driver of economic growth and technological leadership, especially in the current post-epidemic era. In this background, fiscal policy has become an important tool for the Chinese government to shape and promote the development of high-end manufacturing. This paper examines the impact of various fiscal measures, including infrastructure investments, R&D expenditures, tax incentives and subsidies, on the growth and global competitiveness of China’s high-end manufacturing sector. Meanwhile, the research provides an in-depth analysis of specific cases, such as the progress made by the semiconductor industry under the "Made in China 2025" initiative, to illustrate the effectiveness of these interventions. The results show that these interventions have led to significant positive outcomes, such as increased innovation and production capacity. However, it also explores the challenges posed by the misallocation of capital, which can undermine the optimal allocation of resources. Therefore, the research concludes that while fiscal policy has played a key role in promoting the development of high-end manufacturing in China, continuous strategic planning is essential to ensure sustainable growth and sustained technological progress.